Cadastral Registration as Management Function of the Russian Federation Land Fund - E. N. Malanina (Сибирское юридическое обозрение, 2012)
The separate function of the land fund government management – cadastral registration of land – is being analyzed in the article. The author recounts the origin and development of this function, and stresses its shortcomings influencing the efficiency of governmental management in the sphere of land relations.